Identity as a moderator of the association between minority stress and stress physiology - Cook, Mary, author; Quirk, Kelley, advisor; Haddock, Shelley, committee member; Carlson, Laurie, committee member (Colorado State University. Libraries, 2022)
Lesbian, gay, bisexual, transgender, queer or questioning, and other sexual and gender minority identifying (LGBTQ+) youth are at increased risk for experiencing a multitude of social and structural disparities compared to their cisgender, heterosexual counterparts. These include but are not limited to higher rates of childhood abuse, school bullying, victimization, and discrimination. The cumulative negative impact of these factors on health is known as minority stress. Much of the existing research on minority stress in LGBTQ+ adolescents has focused on psychological outcomes, such as anxiety and suicidal ideation. Fortunately, previous research has identified several protective factors against negative mental health outcomes, including identity pride, mindfulness, and community connectedness. Drawing from Minority Stress Theory and Identity Theory, we hypothesized a significant association between minority stress and physical health indicators (i.e., stress physiology) (hypothesis 1). We additionally hypothesized that identity pride (hypothesis 2), mindfulness (hypothesis 3), and community connectedness (hypothesis 4) would moderate this relationship. To test these hypotheses, we administered 21 LGBTQ+ adolescents, ages 12 to 18, an online survey measuring the target variables. A multiple regression was conducted to test main effects and moderators. Results revealed support for all four hypotheses. In other words, minority stress was positively associated with stress physiology (B= .38, p < .001). Identity pride (B = -.13, p= .04), mindfulness (B = .21, p < .001), and community connectedness (B= -.20, p =.02) significantly moderated the association between minority stress and stress physiology. These associations indicate that for participants who reported higher levels of one or more of the variables, identity pride, mindfulness, and community connectedness, the association between minority stress and stress physiology was weakened.
Keywords: connectedness; mindfulness; stress; LGBTQ+; adolescents; pride